2017
DOI: 10.1038/s41598-017-11044-z
|View full text |Cite
|
Sign up to set email alerts
|

Early X chromosome inactivation during human preimplantation development revealed by single-cell RNA-sequencing

Abstract: In female mammals, one X chromosome is transcriptionally inactivated (XCI), leading to dosage compensation between sexes, fundamental for embryo viability. A previous study using single-cell RNA-sequencing (scRNA-seq) data proposed that female human preimplantation embryos achieve dosage compensation by downregulating both Xs, a phenomenon named dampening of X expression. Using a novel pipeline on those data, we identified a decrease in the proportion of biallelically expressed X-linked genes during developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
73
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 36 publications
4
73
1
2
Order By: Relevance
“…Generally, accumulation of H3K27me3 results in XC inactivation in females for dosage compensation. 35,41 Pereira et al supposed the dosage compensation in human is more likely contributed to XC inactivation. In mouse, the paternal XC is inactive in early cleaving embryos, followed by reactivation in the ICM of blastocyst (excluding TE), and then random XC inactivation happens in the epiblast of the female embryo.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, accumulation of H3K27me3 results in XC inactivation in females for dosage compensation. 35,41 Pereira et al supposed the dosage compensation in human is more likely contributed to XC inactivation. In mouse, the paternal XC is inactive in early cleaving embryos, followed by reactivation in the ICM of blastocyst (excluding TE), and then random XC inactivation happens in the epiblast of the female embryo.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent analyses of early human embryos indicate that XIST is expressed in human ICM cells along with apparent dosage compensation (Petropoulos et al, 2016). Nevertheless, there is still a debate as to whether in these cells, X-linked genes are expressed mostly monoallelically, representing initiation of XCI, or biallelically, reflecting the dampening of expression by an unknown mechanism (Petropoulos et al, 2016;Moreira de Mello et al, 2017).…”
Section: Chromosome Inactivationmentioning
confidence: 99%
“…Recently, De Mello and colleagues used a novel pipeline to investigate the same scRNA-Seq dataset of human pre-implantation embryos reported by Petropoulos et al [6] and provided evidence for initiation of X-inactivation [7] (Fig 1). In their analysis, genes in the pseudo autosomal regions (PAR) of the X-chromosome were excluded as they are known to escape X-inactivation.…”
mentioning
confidence: 95%
“…However, X-chromosome dynamics in human pre-implantation embryos remains elusive, largely due to the restricted availability of human embryos and technical difficulties. Two recent studies, by Petropoulos et al [6] and De Mello et al [7], used singlecell RNA-Sequencing (scRNA-Seq) to investigate dosage compensation in human pre-implantation embryos and yielded conflicting models: X-dampening versus X-inactivation. One study showed progressive accumulation of XIST on one of the X-chromosomes along with the inactivation of X-linked genes in pre-implantation female embryos [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation